Preparation method and application of graphene anti-corrosion coating for port machinery surface protection

By using graphene oxide composite materials and hybrid nanomaterials in graphene anticorrosion coatings, the problem of insufficient waterproof and salt spray resistance in the existing technology is solved, and more efficient port mechanical surface protection is achieved, and equipment service life is extended And improves the wear resistance of the coating.

CN117487427BActive Publication Date: 2024-12-13QINGDAO ZHONGFU FLUOROCARBON MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311321965.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-13
Publication Date
2024-12-13
Estimated Expiration
2043-10-13

AI Technical Summary

Technical Problem

The existing graphene anticorrosion coatings have poor waterproofing and salt spray resistance, making it difficult to effectively protect the port machinery surface from corrosion and damage.

Method used

Graphene oxide composite materials and hybrid nanomaterials are used to prepare graphene anticorrosion coatings with high surface area and special structures through ultrasonication, stirring and freeze-drying, which enhances the barrier properties and adhesion of the coating to form a more solid protection. layer.

Benefits of technology

It significantly improves the salt spray and water resistance of graphene anticorrosion coatings, extends the service life of port machinery, and provides better protection in the marine environment, enhancing the mechanical strength and wear resistance of the coating.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

This invention discloses a method for preparing and applying a graphene anti-corrosion coating for surface protection of port machinery. The graphene anti-corrosion coating of this invention is obtained through the following steps: preparing an emulsion, preparing graphene oxide sheets, preparing graphene oxide composite materials, preparing hybrid nanomaterials, and preparing the graphene anti-corrosion coating. Compared with existing technologies, the graphene anti-corrosion coating prepared by this invention exhibits excellent chemical stability and corrosion resistance, effectively protecting the surface of port machinery from corrosion damage and extending its service life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of coatings, and in particular to a preparation method and application of a graphene anti-corrosion coating for surface protection of port machinery. Background Art

[0002] At present, there are a variety of existing technologies for graphene anti-corrosion coatings in the field of port machinery surface protection. Graphene anti-corrosion coating is an innovative coating formula designed to protect the surface of port machinery from corrosion and damage. It uses graphene as a key ingredient and has excellent anti-corrosion and weather resistance while providing excellent adhesion and wear resistance. The protective layer formed by the coating can effectively isolate moisture, salt spray, chemicals and ultraviolet radiation in the port environment, extend the service life of machinery and equipment and reduce maintenance costs.

[0003] The following are several common graphene anti-corrosion coating technologies: Graphene composite coating: Graphene is compounded with other anti-corrosion materials (such as polymers, ceramics, etc.) to form a coating with excellent anti-corrosion properties. The addition of graphene can enhance the mechanical strength, corrosion resistance and weather resistance of the coating. Graphene modified coating: Graphene is modified with traditional anti-corrosion coatings by chemical methods to improve the performance of the coating. Graphene can form a uniform dispersion structure in the coating to improve the corrosion resistance, adhesion and wear resistance of the coating. Graphene coating technology: Graphene coating is formed on the surface of port machinery by utilizing the high electrical conductivity and high thermal conductivity of graphene. This coating can provide good anti-corrosion performance and has the characteristics of electrical and thermal conductivity, and can be used for anti-static, lightning protection and other applications. Graphene nanosheet coating: Graphene coating with nanometer thickness is prepared by utilizing the nanosheet structure of graphene. This coating has excellent anti-corrosion performance and optical properties, and can be used for the protection and repair of the surface of port machinery. These technologies have certain application potential in improving the surface protection performance of port machinery.

[0004] The waterproof performance and salt spray resistance of the graphene anti-corrosion coating in the prior art need to be further improved.

[0005] China's authorized invention patent CN105086758B discloses a method for preparing a graphene anticorrosive coating, wherein the coating comprises a component A that can be cured into a film and a component B containing a curing agent; wherein the component A comprises the following components by mass percentage: 0.1-5wt% graphene; 0-35wt% zinc powder; 30-70wt% filler; 10-20wt% epoxy resin with a solid content of 54%; 10-20wt% solvent; wherein the sum of the mass percentages of graphene, zinc powder and filler is 60-80wt%, and the sum of the mass percentages of the components of the component A is 100w%. The invention adds graphene to the anticorrosive coating, greatly reducing the thickness of the coating film; by selecting the components, while improving the anticorrosion effect, the content of zinc powder is greatly reduced, overcoming the anticorrosion method of zinc-rich coating at the expense of zinc powder, greatly reducing the zinc oxide mist generated during welding, and being environmentally friendly. However, the waterproof performance and salt spray resistance of the graphene anti-corrosion coating prepared by this invention are poor. Summary of the invention

[0006] In view of the shortcomings of the prior art graphene anti-corrosion coatings, which have poor waterproof and salt spray resistance, the technical problem to be solved by the present invention is to provide a preparation method and application of a graphene anti-corrosion coating for surface protection of port machinery with good waterproof and salt spray resistance.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions:

[0008] A method for preparing a graphene anticorrosive coating for surface protection of port machinery is as follows:

[0009] Step 1, adding ammonium persulfate, a surfactant, sodium hexadecyl sulfate and sodium bicarbonate into water to obtain a mixed solution; then, adding 2-methylprop-2-enoic acid, glycidyl methacrylate, isoeugenol methyl ether, butyl acrylate, silane coupling agent KH-570, N,N'-methylenebisacrylamide and epoxy resin into water, stirring to obtain a composite monomer mixture, dropping the mixed solution into the composite monomer mixture, and then continuously stirring at high temperature, cooling to room temperature, adding ammonia water to adjust the pH value, filtering to obtain an emulsion;

[0010] Step 2, adding graphite to sulfuric acid and stirring, then adding potassium permanganate and sodium nitrate, stirring, diluting with water, and then adding hydrogen peroxide to obtain graphene oxide sheets; washing with hydrochloric acid and water respectively, and vacuum drying at room temperature to obtain dry graphene oxide sheets;

[0011] Step 3, adding the dried graphene oxide sheet prepared in step 2 to hydrochloric acid, ultrasonicating to obtain a uniform solution, then adding 3,4-(methylenedioxy)aniline to water to obtain solution A, mixing solution A with the uniform solution, stirring at low temperature, adding hydrochloric acid containing ammonium persulfate during stirring, stirring at low temperature, washing with water and anhydrous ethanol until the filtrate is colorless, ultrasonicating, adjusting the pH with ammonia water, washing with water, and drying to obtain a graphene oxide composite material;

[0012] Step 4, adding carboxymethyl chitosan to water, stirring to obtain a carboxymethyl chitosan solution, adding the dried graphene oxide sheets prepared in step 2 to water and ultrasonicating to obtain a graphene oxide suspension, then adding the graphene oxide suspension to the carboxymethyl chitosan solution, stirring, adding hydrazine hydrate, stirring at high temperature, filtering, washing with water, and freeze-drying to obtain a hybrid nanomaterial;

[0013] Step 5: Add zinc powder, defoamer, dispersant, organic bentonite, silicon dioxide and pentaethylenehexamine to the emulsion prepared in step 1, stir to form a zinc-based water-based latex; add the hybrid nanomaterial prepared in step 4, N,N'-bis(4-aminophenyl)-1.4-benzoquinonediamine and the graphene oxide composite material prepared in step 3, and stir at room temperature to obtain a graphene anti-corrosion coating.

[0014] Preferably, the preparation method of the graphene anti-corrosion coating for port machinery surface protection is as follows, in parts by weight:

[0015] Step 1, adding 1 to 1.5 parts of ammonium persulfate, 2 to 3 parts of a surfactant, 0.5 to 1 part of sodium n-hexadecyl sulfate and 0.4 to 0.6 parts of sodium bicarbonate to 30 to 50 parts of water to obtain a mixed solution; then, adding 1 to 3 parts of 2-methylprop-2-enoic acid, 10 to 15 parts of glycidyl methacrylate, 8 to 12 parts of isoeugenol methyl ether, 18 to 22 parts of butyl acrylate, 2 to 2.5 parts of a silane coupling agent KH-570, 0.4 to 0.6 parts of N, N'-methylenebisacrylamide and 15 to 25 parts of an epoxy resin to 60 to 70 parts of water, stirring to obtain a composite monomer mixture, dripping the mixed solution into the composite monomer mixture at a dripping speed of 0.5 to 2 mL / min, then continuously stirring at 70 to 85° C., cooling to room temperature, adding 20 to 27 wt % ammonia water to adjust the pH value to 7.0 to 8.0, filtering with a molecular sieve to obtain an emulsion;

[0016] Step 2, adding 1 to 3 parts of graphite to 180 to 220 parts of 70 to 85 wt% sulfuric acid and stirring, then adding 10 to 15 parts of potassium permanganate and 1 to 3 parts of sodium nitrate, stirring, diluting with 800 to 1200 parts of water, and then adding 8 to 12 parts of 25 to 33 wt% hydrogen peroxide to obtain graphene oxide sheets; washing with 0.5 to 2 mol / L hydrochloric acid and water for 1 to 3 times respectively, and vacuum drying at room temperature to obtain dry graphene oxide sheets;

[0017] Step 3, adding 0.05-0.2 parts of the dried graphene oxide sheet prepared in step 2 to 15-25 parts of 0.5-2 mol / L hydrochloric acid, ultrasonicating to obtain a uniform solution, and then adding 0.5-2 parts of 3,4-(methylenedioxy)aniline to 15-25 parts of water to obtain solution A, mixing solution A with the uniform solution, stirring at 1-5°C, adding 4-6 parts of 0.5-2 mol / L hydrochloric acid containing 0.5-2 parts of ammonium persulfate during the stirring process, stirring at 1-5°C, washing with water and anhydrous ethanol until the filtrate is colorless, ultrasonicating, adjusting the pH to 10-11 with 20-27wt% ammonia water, washing with water, and vacuum drying at 70-85°C for 10-30h to obtain a graphene oxide composite material;

[0018] Step 4, adding 0.1-0.3 parts of carboxymethyl chitosan to 90-110 parts of water, stirring to obtain a carboxymethyl chitosan solution, adding 0.1-0.3 parts of the dried graphene oxide sheets prepared in step 2 to 80-120 parts of water for ultrasonication to obtain a graphene oxide suspension, then adding 80-120 parts of the graphene oxide suspension to the carboxymethyl chitosan solution, stirring, adding 0.1-0.3 parts of hydrazine hydrate, stirring at 80-95° C., filtering, washing with water, and freeze-drying to obtain a hybrid nanomaterial;

[0019] Step 5, adding 40-60 parts of zinc powder, 0.3-0.5 parts of defoaming agent, 0.6-0.7 parts of dispersant, 1-3 parts of organic bentonite, 0.1-0.2 parts of silicon dioxide, and 0.1-0.2 parts of pentaethylenehexamine to 20-30 parts of the emulsion prepared in step 1, stirring to form a zinc-based water-based latex; adding 0.2-0.4 parts of the hybrid nanomaterial prepared in step 4, 0.4-0.6 parts of N,N'-bis(4-aminophenyl)-1.4-benzoquinonediamine, and 0.4-0.6 parts of the graphene oxide composite material prepared in step 3, and stirring at room temperature to obtain a graphene anti-corrosion coating.

[0020] Preferably, the surfactant is at least one of OP-10, NP-9 or AES.

[0021] Preferably, the molecular sieve is 800-1000Da.

[0022] Preferably, the defoaming agent is at least one of SXP-105, SN-345, BYK-045, and BYK-141.

[0023] Preferably, the dispersant is at least one of SN-5040, GH5050, DP512, BYK-110, DisuperS18, DisuperS19, and DisuperS31.

[0024] Preferably, the stirring speed is independently 100 to 500 rpm, and the stirring time is independently 0.1 to 72 h.

[0025] Preferably, the ultrasonic time is independently 10 to 60 min, the ultrasonic frequency is independently 20 to 60 kHz, and the ultrasonic power is independently 100 to 400 W.

[0026] The application of the graphene anti-corrosion coating for the surface protection of port machinery is mainly used in marine engineering facilities; the marine engineering facilities include offshore facilities, coastal and bay structures, offshore oil platforms, and boats.

[0027] Layered graphene oxide composites have a certain blocking effect on the permeation of oxygen and water. When graphene oxide composites are not used, the permeation of oxygen and water into the coating increases, while when graphene oxide composites are added, the high surface area of ​​the graphene oxide composites bypasses the diffusion path of oxygen and water, thereby greatly reducing the permeation rate of oxygen and water through the coating.

[0028] Graphene oxide composite materials have good conductivity due to their flaky structure, which can enhance the conductivity of the coating and facilitate the connection between zinc powder and the conductive network. For coatings with only zinc powder added, the zinc powder particles have a good sacrificial protection effect in the early stage of the coating, but as the use time increases, the corrosive medium accumulates in the coating, causing pores in the zinc powder particles, making it easier for the graphene oxide composite materials to penetrate into the steel matrix, reducing the adhesion of the coating to the steel. Due to the low electrical contact between zinc and zinc or the substrate, only a part of the zinc powder can enter the conductive network in the coating, and the other part of the zinc powder is gradually oxidized and converted into non-conductive zinc oxide or zinc hydroxide during the immersion process, resulting in a decrease in cathodic protection ability until the cathodic protection is lost. Therefore, the cathodic protection of only adding zinc powder is much less than that of adding graphene oxide composite materials.

[0029] N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine with poor dispersibility and high porosity does not have good cathodic protection performance in the coating, while the dispersibility of N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine in zinc powder particles is crucial to improving the electronic conductivity of N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine and enhancing its cathodic protection performance. The addition of graphene oxide composites can improve the barrier performance of graphene oxide to the diffusion of oxygen and water through the pore space of zinc powder particles, thereby improving the anti-corrosion time to a certain extent.

[0030] The good dispersibility of hybrid nanomaterials can be attributed to the water solubility of carboxyl groups and the electrostatic repulsion between molecules. The presence of carboxymethyl chitosan on the surface of hybrid nanomaterials promotes the interfacial interaction between hybrid nanomaterials and polymer matrix, and hybrid nanomaterials can be uniformly embedded in zinc-based water-based latex. Well-dispersed hybrid nanomaterials can significantly improve the barrier properties of the coating. This may be because the dispersion of hybrid nanomaterials in the coating will produce a "maze effect", which can well inhibit the penetration of corrosive media, thereby enhancing the barrier properties of the coating. In addition, grafting carboxymethyl chitosan on the surface of graphene oxide can prevent the direct connection of graphene-graphene and graphene-steel, thereby inhibiting the occurrence of galvanic corrosion, and has excellent salt spray and water resistance.

[0031] Graphene oxide composites and hybrid nanomaterials play a synergistic role in graphene anti-corrosion coatings, which is beneficial to improve their salt spray and water resistance. Graphene oxide composites and hybrid nanomaterials can fill the pores and defects in the coating, reduce the possibility of salt spray and moisture entering the interior of the coating, and thus improve the anti-penetration performance of the coating. The conductive properties of graphene oxide composites help to form a protective layer on the surface of the coating, improve the resistance of the coating, and thus reduce the occurrence of electrochemical reactions and metal corrosion. The high strength of graphene oxide combined with the bonding properties of carboxymethyl chitosan can enhance the mechanical strength and wear resistance of the coating and reduce the peeling and damage of the coating. In summary, the synergistic effect of graphene oxide composites and hybrid nanomaterials in graphene anti-corrosion coatings can improve its salt spray and water resistance, enhance the protective effect of the coating, and extend the service life of port machinery.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] 1) The graphene anti-corrosion coating prepared by the present invention has excellent chemical stability and corrosion resistance, and can effectively protect the surface of port machinery from corrosion damage and extend its service life.

[0034] 2) The graphene anti-corrosion coating prepared by the present invention has a high surface area and a special structure, which can enhance the adhesion between the coating and the substrate and provide a more solid protective layer.

[0035] 3) The graphene anti-corrosion coating prepared by the present invention has excellent wear resistance and weather resistance, enabling it to withstand the influence of mechanical wear, ultraviolet radiation and climatic factors in the port environment for a long time.

[0036] 4) The graphene anti-corrosion coating prepared by the present invention has excellent waterproof performance, which can prevent moisture from penetrating into the surface of port machinery and reduce the corrosion of the machinery in a humid environment; it also has better salt spray resistance and can provide better protection in a marine environment. DETAILED DESCRIPTION

[0037] Main sources of substances:

[0038] Surfactant OP-10: Jinan Xinshuangyue Chemical Co., Ltd., model: 99.

[0039] Epoxy resin: Zhengzhou Penghui Chemical Products Co., Ltd., brand: cydw-100.

[0040] Silane coupling agent KH-570: Dongguan Shanyi Plastic Chemical Co., Ltd., item number: KH-570.

[0041] Defoaming agent SXP-105: Suzhou China Resources Chemical Co., Ltd., model: SXP-105.

[0042] Dispersant SN-5040: Guangzhou Shenhong Chemical Co., Ltd., model: 5040.

[0043] Carboxymethyl chitosan: Shaanxi Baichuan Biotechnology Co., Ltd., product number: bc20180524-2.

[0044] Organic bentonite: Zhejiang Kangbaixin New Materials Co., Ltd., model: CP-100.

[0045] N,N'-bis(4-aminophenyl)-1,4-benzoquinonediiamine: English name: N,N'-bis(4-aminophenyl)-1,4-benzoquinonediimine, CAS: 264146-78-3.

[0046] Zinc powder: Guangzhou Jinkai Chemical Co., Ltd., item number: 1759104001.

[0047] Silica: Jinan DeLan Chemical Co., Ltd., model: DL-805.

[0048] Polyaniline: Shandong Jiaying Chemical Technology Co., Ltd., model: 0.

[0049] Example 1

[0050] A method for preparing a graphene anticorrosive coating for surface protection of port machinery is as follows:

[0051] Step 1, adding 1.4g ammonium persulfate, 2.5g surfactant OP-10, 0.8g sodium hexadecyl sulfate and 0.5g sodium bicarbonate to 40g water to obtain a mixed solution; then, adding 2g 2-methylprop-2-enoic acid, 12g glycidyl methacrylate, 10g isoeugenol methyl ether, 20g butyl acrylate, 2.2g silane coupling agent KH-570, 0.5g N, N'-methylenebisacrylamide and 20g epoxy resin to 65g water, stirring at 200rpm for 2h to obtain a composite monomer mixture, dripping the mixed solution into the composite monomer mixture at a dropping speed of 1mL / min, then stirring continuously at 300rpm at 80°C for 4h, cooling to room temperature, adding 25wt% ammonia water to adjust the pH value to 8.0, filtering with a 1000Da molecular sieve to obtain an emulsion;

[0052] Step 2, adding 2g of graphite to 200g of 80wt% sulfuric acid and stirring at 200rpm for 2h, then adding 12g of potassium permanganate and 2g of sodium nitrate, stirring at 200rpm for 72h, diluting with 1000g of water, and then adding 10g of 30wt% hydrogen peroxide to obtain graphene oxide sheets; washing with 1mol / L hydrochloric acid and water for 3 times respectively, and vacuum drying at room temperature to obtain dry graphene oxide sheets;

[0053] Step 3, adding 0.1g of the dried graphene oxide sheet prepared in step 2 to 20g of 1mol / L hydrochloric acid, ultrasonically treating for 30min at a frequency of 40kHz and a power of 200W to obtain a uniform solution, then adding 1g of 3,4-(methylenedioxy)aniline to 20g of water to obtain solution A, mixing solution A with the uniform solution, stirring at 200rpm for 30min at 4°C, adding 5g of 1mol / L hydrochloric acid containing 1g of ammonium persulfate during the stirring process, stirring at 200rpm for 24h at 4°C, washing with water and anhydrous ethanol until the filtrate is colorless, ultrasonically treating for 30min at a frequency of 40kHz and a power of 200W, adjusting the pH to 11 with 25wt% ammonia water, washing with water, and vacuum drying at 80°C for 24h to obtain a graphene oxide composite material;

[0054] Step 4: add 0.2 g of carboxymethyl chitosan to 100 g of water, stir at 200 rpm for 3 h to obtain a carboxymethyl chitosan solution, add 0.2 g of the dried graphene oxide sheet prepared in step 2 to 100 g of water, ultrasonicate for 1 h, the ultrasonic frequency is 40 kHz, and the ultrasonic power is 300 W to obtain a graphene oxide suspension; then add 100 g of the graphene oxide suspension to the carboxymethyl chitosan solution, stir at 200 rpm for 1 h, add 0.2 g of hydrazine hydrate, stir at 200 rpm at 90 ° C for 1 h, filter, wash with water, and freeze-dry to obtain a hybrid nanomaterial;

[0055] Step 5: Add 50 g zinc powder, 0.4 g defoamer SXP-105, 0.65 g dispersant SN-5040, 2 g organic bentonite, 0.15 g silicon dioxide and 0.17 g pentaethylenehexamine to 25 g of the emulsion prepared in step 1, and stir at 200 rpm for 30 min to form a zinc-based aqueous latex; add 0.3 g of the hybrid nanomaterial prepared in step 4, 0.5 g of N, N'-bis(4-aminophenyl)-1.4-benzoquinonediamine and 0.5 g of the graphene oxide composite material prepared in step 3, and stir at 200 rpm for 3 h at room temperature to obtain a graphene anticorrosion coating.

[0056] Comparative Example 1

[0057] A method for preparing a graphene anticorrosive coating for surface protection of port machinery is as follows:

[0058] Step 1, adding 1.4g ammonium persulfate, 2.5g surfactant OP-10, 0.8g sodium hexadecyl sulfate and 0.5g sodium bicarbonate to 40g water to obtain a mixed solution; then, adding 2g 2-methylprop-2-enoic acid, 12g glycidyl methacrylate, 10g isoeugenol methyl ether, 20g butyl acrylate, 2.2g silane coupling agent KH-570, 0.5g N, N'-methylenebisacrylamide and 20g epoxy resin to 65g water, stirring at 200rpm for 2h to obtain a composite monomer mixture, dripping the mixed solution into the composite monomer mixture at a dropping speed of 1mL / min, then stirring continuously at 300rpm at 80°C for 4h, cooling to room temperature, adding 25wt% ammonia water to adjust the pH value to 8.0, filtering with a 1000Da molecular sieve to obtain an emulsion;

[0059] Step 2, adding 2g of graphite to 200g of 80wt% sulfuric acid and stirring at 200rpm for 2h, then adding 12g of potassium permanganate and 2g of sodium nitrate, stirring at 200rpm for 72h, diluting with 1000g of water, and then adding 10g of 30wt% hydrogen peroxide to obtain graphene oxide sheets; washing with 1mol / L hydrochloric acid and water for 3 times respectively, and vacuum drying at room temperature to obtain dry graphene oxide sheets;

[0060] Step 3, adding 0.2g of carboxymethyl chitosan to 100g of water, stirring at 200rpm for 3h to obtain a carboxymethyl chitosan solution, adding 0.2g of the dried graphene oxide sheet prepared in step 2 to 100g of water for 1h, the ultrasonic frequency is 40kHz, and the ultrasonic power is 300W to obtain a graphene oxide suspension; then adding 100g of the graphene oxide suspension to the carboxymethyl chitosan solution, stirring at 200rpm for 1h, adding 0.2g of hydrazine hydrate, stirring at 200rpm at 90°C for 1h, filtering, washing with water, and freeze-drying to obtain a hybrid nanomaterial;

[0061] Step 4: Add 50g zinc powder, 0.4g defoamer SXP-105, 0.65g dispersant SN-5040, 2g organic bentonite, 0.15g silicon dioxide, and 0.17g pentaethylenehexamine to 25g of the emulsion prepared in step 1, and stir at 200rpm for 30min to form a zinc-based aqueous latex; add 0.3g of the hybrid nanomaterial prepared in step 3, 0.5g of N,N'-bis(4-aminophenyl)-1.4-benzoquinonediamine, and 0.5g of the dried graphene oxide sheet prepared in step 2, and stir at 200rpm for 3h at room temperature to obtain a graphene anticorrosion coating.

[0062] Comparative Example 2

[0063] A method for preparing a graphene anticorrosive coating for surface protection of port machinery is as follows:

[0064] Step 1, adding 1.4g ammonium persulfate, 2.5g surfactant OP-10, 0.8g sodium hexadecyl sulfate and 0.5g sodium bicarbonate to 40g water to obtain a mixed solution; then, adding 2g 2-methylprop-2-enoic acid, 12g glycidyl methacrylate, 10g isoeugenol methyl ether, 20g butyl acrylate, 2.2g silane coupling agent KH-570, 0.5g N, N'-methylenebisacrylamide and 20g epoxy resin to 65g water, stirring at 200rpm for 2h to obtain a composite monomer mixture, dripping the mixed solution into the composite monomer mixture at a dropping speed of 1mL / min, then stirring continuously at 300rpm at 80°C for 4h, cooling to room temperature, adding 25wt% ammonia water to adjust the pH value to 8.0, filtering with a 1000Da molecular sieve to obtain an emulsion;

[0065] Step 2, adding 2g of graphite to 200g of 80wt% sulfuric acid and stirring at 200rpm for 2h, then adding 12g of potassium permanganate and 2g of sodium nitrate, stirring at 200rpm for 72h, diluting with 1000g of water, and then adding 10g of 30wt% hydrogen peroxide to obtain graphene oxide sheets; washing with 1mol / L hydrochloric acid and water for 3 times respectively, and vacuum drying at room temperature to obtain dry graphene oxide sheets;

[0066] Step 3, adding 0.1g of the dried graphene oxide sheet prepared in step 2 to 20g of 1mol / L hydrochloric acid, ultrasonically treating for 30min at a frequency of 40kHz and a power of 200W to obtain a uniform solution, then adding 1g of 3,4-(methylenedioxy)aniline to 20g of water to obtain solution A, mixing solution A with the uniform solution, stirring at 200rpm for 30min at 4°C, adding 5g of 1mol / L hydrochloric acid containing 1g of ammonium persulfate during the stirring process, stirring at 200rpm for 24h at 4°C, washing with water and anhydrous ethanol until the filtrate is colorless, ultrasonically treating for 30min at a frequency of 40kHz and a power of 200W, adjusting the pH to 11 with 25wt% ammonia water, washing with water, and vacuum drying at 80°C for 24h to obtain a graphene oxide composite material;

[0067] Step 4: Add 50g zinc powder, 0.4g defoamer SXP-105, 0.65g dispersant SN-5040, 2g organic bentonite, 0.15g silicon dioxide, and 0.17g pentaethylenehexamine to 25g of the emulsion prepared in step 1, and stir at 200rpm for 30min to form a zinc-based water-based latex; add 0.3g of the dried graphene oxide sheets prepared in step 2, 0.5g of N,N'-bis(4-aminophenyl)-1.4-benzoquinonediamine, and 0.5g of the graphene oxide composite material prepared in step 3, and stir at 200rpm for 3h at room temperature to obtain a graphene anti-corrosion coating.

[0068] Comparative Example 3

[0069] A method for preparing a graphene anticorrosive coating for surface protection of port machinery is as follows:

[0070] Step 1, adding 1.4g ammonium persulfate, 2.5g surfactant OP-10, 0.8g sodium hexadecyl sulfate and 0.5g sodium bicarbonate to 40g water to obtain a mixed solution; then, adding 2g 2-methylprop-2-enoic acid, 12g glycidyl methacrylate, 10g isoeugenol methyl ether, 20g butyl acrylate, 2.2g silane coupling agent KH-570, 0.5g N, N'-methylenebisacrylamide and 20g epoxy resin to 65g water, stirring at 200rpm for 2h to obtain a composite monomer mixture, dripping the mixed solution into the composite monomer mixture at a dropping speed of 1mL / min, then stirring continuously at 300rpm at 80°C for 4h, cooling to room temperature, adding 25wt% ammonia water to adjust the pH value to 8.0, filtering with a 1000Da molecular sieve to obtain an emulsion;

[0071] Step 2, adding 2g of graphite to 200g of 80wt% sulfuric acid and stirring at 200rpm for 2h, then adding 12g of potassium permanganate and 2g of sodium nitrate, stirring at 200rpm for 72h, diluting with 1000g of water, and then adding 10g of 30wt% hydrogen peroxide to obtain graphene oxide sheets; washing with 1mol / L hydrochloric acid and water for 3 times respectively, and vacuum drying at room temperature to obtain dry graphene oxide sheets;

[0072] Step 3, adding 0.1g of the graphene oxide sheet prepared in step 2 to 20g of 1mol / L hydrochloric acid, ultrasonically treating for 30min, at an ultrasonic frequency of 40kHz and an ultrasonic power of 200W, to obtain a uniform solution, then adding 1g of 3,4-(methylenedioxy)aniline to 20g of water to obtain solution A, mixing solution A with the uniform solution, stirring at 200rpm for 30min at 4°C, adding 5g of 1mol / L hydrochloric acid containing 1g of ammonium persulfate during the stirring process, stirring at 200rpm for 24h at 4°C, washing with water and anhydrous ethanol until the filtrate is colorless, ultrasonically treating for 30min, at an ultrasonic frequency of 40kHz and an ultrasonic power of 200W, adjusting the pH to 11 with 25wt% ammonia water, washing with water, and vacuum drying at 80°C for 24h to obtain a graphene oxide composite material;

[0073] Step 4: add 0.2 g of carboxymethyl chitosan to 100 g of water, stir at 200 rpm for 3 h to obtain a carboxymethyl chitosan solution, add 0.2 g of the graphite oxide prepared in step 2 to 100 g of water for ultrasonic 1 h, the ultrasonic frequency is 40 kHz, and the ultrasonic power is 300 W to obtain a graphene oxide suspension; then add 100 g of the graphene oxide suspension to the carboxymethyl chitosan solution, stir at 200 rpm for 1 h, add 0.2 g of hydrazine hydrate, stir at 200 rpm at 90 ° C for 1 h, filter, wash with water, and freeze-dry to obtain a hybrid nanomaterial;

[0074] Step 5: Add 50 g zinc powder, 0.4 g defoamer SXP-105, 0.65 g dispersant SN-5040, 2 g organic bentonite, 0.15 g silicon dioxide and 0.17 g pentaethylenehexamine to 25 g of the emulsion prepared in step 1, and stir at 200 rpm for 30 min to form a zinc-based aqueous latex; add 0.3 g of the hybrid nanomaterial prepared in step 4, 0.5 g of polyaniline and 0.5 g of the graphene oxide composite material prepared in step 3, and stir at 200 rpm for 3 h at room temperature to obtain a graphene anticorrosion coating.

[0075] Comparative Example 4

[0076] A method for preparing a graphene anticorrosive coating for surface protection of port machinery is as follows:

[0077] Step 1, adding 1.4g ammonium persulfate, 2.5g surfactant OP-10, 0.8g sodium hexadecyl sulfate and 0.5g sodium bicarbonate to 40g water to obtain a mixed solution; then, adding 2g 2-methylprop-2-enoic acid, 12g glycidyl methacrylate, 10g isoeugenol methyl ether, 20g butyl acrylate, 2.2g silane coupling agent KH-570, 0.5g N, N'-methylenebisacrylamide and 20g epoxy resin to 65g water, stirring at 200rpm for 2h to obtain a composite monomer mixture, dripping the mixed solution into the composite monomer mixture at a dropping speed of 1mL / min, then stirring continuously at 300rpm at 80°C for 4h, cooling to room temperature, adding 25wt% ammonia water to adjust the pH value to 8.0, filtering with a 1000Da molecular sieve to obtain an emulsion;

[0078] Step 2, adding 2g of graphite to 200g of 80wt% sulfuric acid and stirring at 200rpm for 2h, then adding 12g of potassium permanganate and 2g of sodium nitrate, stirring at 200rpm for 72h, diluting with 1000g of water, and then adding 10g of 30wt% hydrogen peroxide to obtain graphene oxide sheets; washing with 1mol / L hydrochloric acid and water for 3 times respectively, and vacuum drying at room temperature to obtain dry graphene oxide sheets;

[0079] Step 3, add 50g zinc powder, 0.4g defoamer SXP-105, 0.65g dispersant SN-5040, 2g organic bentonite, 0.15g silica, and 0.17g pentaethylenehexamine to 25g of the emulsion prepared in step 1, and stir at 200rpm for 30min to form a zinc-based water-based latex; add 0.8g of the dried graphene oxide sheets prepared in step 2 and 0.5g of polyaniline, and stir at 200rpm for 3h at room temperature to obtain a graphene anti-corrosion coating.

[0080] Test Example 1

[0081] Salt spray resistance test

[0082] Sample pretreatment: The tinplate is selected to have a specification of 50mmx130mmx0.8mm, and is polished with sandpaper to remove rust, then cleaned several times with deionized water and ethanol solution, and dried for use. Coating preparation: The roller coating method is adopted, and the coating of the embodiment of the present invention and the comparative example is evenly coated on the surface of the tinplate using a wire rod to ensure that the coating film is uniform and no shrinkage cavities are formed. The coated sample is placed at room temperature for 15 minutes, and then placed in a forced air drying oven to cure at 80°C for 2 hours. The coating thickness after curing is about 45 (±5) μm.

[0083] The neutral salt spray test was carried out according to GB / T1771-2007. The corrosive medium was a 5% sodium chloride aqueous solution. The salt spray chamber was set at 35°C and the salt spray deposition was 1.5 ml (80 cm2 h) -1 , continuous spraying, corrosion time is 1000h, the plate used in the test is tinplate. After corrosion, observe whether there are bubbles, corrosion, or peeling on the surface coating of the test plate, and keep records. The test results are shown in Table 1.

[0084] Table 1 Salt spray resistance test results

[0085] Experimental protocol Salt spray test results Example 1 No bubbles, no rust, no peeling Comparative Example 1 A small amount of bubbles, some rust, a small amount of peeling Comparative Example 2 A small amount of bubbles, some rust, a small amount of peeling Comparative Example 3 A small amount of bubbles, some rust, a small amount of peeling Comparative Example 4 Lots of bubbles, lots of rust, lots of peeling

[0086] Test Example 2

[0087] Water resistance test

[0088] Graphene anti-corrosion coatings used for port machinery surface protection are in water environments for a long time, and water is one of the most important factors causing corrosion. Anti-corrosion coatings are also often used in various environments with high humidity, such as oceans, rivers, sewers, rainy and other harsh environmental conditions. Therefore, the water resistance of the coating is one of the criteria for evaluating its anti-corrosion performance. The better the water resistance of the coating, the easier it is to block the penetration of water molecules, which can greatly delay the occurrence of corrosion and extend the service life of the metal.

[0089] Referring to GB / T30648.2-2015 "Determination of Liquid Resistance of Paints and Varnishes Part 2: Immersion Method", the water resistance of the coatings of the embodiments of the present invention and the comparative examples was tested by immersion method. After 20 days of immersion, the samples were taken out, the water was dried, and dried at room temperature for 24 hours. The coating surface was observed for whitening, bubbling, shedding, etc. The test results are shown in Table 2.

[0090] Table 2 Water resistance test results

[0091] Trial plan Water resistance Example 1 No whitening, no blistering, no shedding Comparative Example 1 Slightly white, no blistering, no shedding Comparative Example 2 Slightly white, no blistering, no shedding Comparative Example 3 Slight whitening, slight bubbling, no shedding Comparative Example 4 Partial whitening, slight blistering, slight peeling

[0092] From the test data of Tables 1 and 2, it can be seen that the graphene anticorrosive coating prepared in Example 1 of the present invention has excellent salt spray resistance and water resistance. Wherein Example 1 of the present invention is compared with Comparative Example 1, the possible reason is that Example 1 adopts graphene oxide composite material, N, N'-bis (4-aminophenyl) -1.4-benzoquinone diamine is adsorbed on the graphene oxide composite material sheet through hydrogen bonding and physical adsorption, and the amino group in N, N'-bis (4-aminophenyl) -1.4-benzoquinone diamine is combined with the carboxyl group in the graphene oxide composite material and the hybrid nanomaterial, and N, N'-bis (4-aminophenyl) -1.4-benzoquinone diamine is grafted onto the graphene oxide composite material sheet, which helps to improve the water dispersibility and conductivity of N, N'-bis (4-aminophenyl) -1.4-benzoquinone diamine. The graphene oxide obtained in step 2 has an irregular layered structure, and due to the large surface energy, part of the graphene oxide agglomerates. However, the graphene oxide composite material retains the lamellar structure of graphene oxide, and the spherical N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine molecules are evenly distributed on the graphene oxide composite flakes instead of agglomerating, which may be due to the good adsorption of the graphene oxide composite material, and the improvement of conductivity may be due to the formation of a conductive path between the N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine molecules and the graphene oxide composite material through superposition interaction. The presence of the graphene oxide composite material increases the conductivity of N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine, and the addition of the graphene oxide composite material improves the dispersibility of N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine in the solution. Since the graphene oxide composite material contains a large number of oxygen-containing polar groups such as hydroxyl, carboxyl, and epoxy groups, the graphene oxide composite material is easy to stably disperse in aqueous solutions and aqueous emulsions. In addition, during the in-situ polymerization process, N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine molecules can easily combine with the graphene oxide composite material through an amidation reaction. Therefore, N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine is uniformly adsorbed on the graphene oxide flakes, which is conducive to the uniform dispersion of N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine in the aqueous solution. The layered graphene oxide composite material has a certain blocking effect on the penetration of oxygen and water. In the case where no graphene oxide composite material is used, the penetration of oxygen and water into the coating increases, while in the case where the graphene oxide composite material is added, the high surface area of ​​the graphene oxide composite material bypasses the diffusion path of oxygen and water, thereby greatly reducing the penetration rate of oxygen and water through the coating.N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine with poor dispersibility and high porosity does not have good cathodic protection performance in the coating, while the dispersibility of N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine in zinc particles is crucial to improving the electronic conductivity of N,N'-bis(4-aminophenyl)-1.4-benzoquinone diamine and enhancing its cathodic protection performance. The addition of graphene oxide composites can improve the barrier performance of graphene oxide to the diffusion of oxygen and water through the pore space of zinc particles, thereby improving the anti-corrosion time to a certain extent and enhancing the salt spray and water resistance of graphene anti-corrosion coatings.

[0093] Compared with Comparative Example 2, Example 1 may be due to the good dispersibility of the hybrid nanomaterial, which can be attributed to the water solubility of the carboxyl group and the electrostatic repulsion between molecules. The presence of carboxymethyl chitosan on the surface of the hybrid nanomaterial promotes the interfacial interaction between the hybrid nanomaterial and the polymer matrix, and the hybrid nanomaterial can be uniformly embedded in the zinc-based aqueous latex. Well-dispersed hybrid nanomaterials can significantly improve the barrier properties of the coating. It may be that the dispersion of the hybrid nanomaterial in the coating will produce a "maze effect", which can well inhibit the penetration of corrosive media, thereby enhancing the barrier properties of the coating. In addition, grafting carboxymethyl chitosan on the surface of graphene oxide can prevent the direct connection of graphene-graphene and graphene-steel, thereby inhibiting the occurrence of galvanic corrosion, and has excellent salt spray resistance and water resistance.

[0094] Compared with Comparative Example 3, Example 1 may be due to the fact that the use of N, N'-bis (4-aminophenyl) -1.4-benzoquinone diamine has advantages in salt spray resistance and water resistance compared to polyaniline. From the perspective of molecular structure, N, N'-bis (4-aminophenyl) -1.4-benzoquinone diamine contains two amino functional groups in its structure. The two amino groups can be more fully combined with the carboxyl groups in the graphene oxide composite material and the hybrid nanomaterial, and the effect of adsorption on the graphene oxide composite material sheet through hydrogen bonding and physical adsorption is better. This structure may give the substance better salt spray resistance and water resistance.

Claims

1. A method for preparing a graphene anti-corrosion coating for surface protection of port machinery, It is characterized in that The preparation method is as follows: Step 1, adding ammonium persulfate, a surfactant, sodium hexadecyl sulfate and sodium bicarbonate into water to obtain a mixed solution; then, adding 2-methylprop-2-enoic acid, glycidyl methacrylate, isoeugenol methyl ether, butyl acrylate, silane coupling agent KH-570, N,N'-methylenebisacrylamide and epoxy resin into water, stirring to obtain a composite monomer mixture, dropping the mixed solution into the composite monomer mixture, and then continuously stirring at high temperature, cooling to room temperature, adding ammonia water to adjust the pH value, filtering with a molecular sieve to obtain an emulsion; Step 2, adding graphite to sulfuric acid and stirring, then adding potassium permanganate and sodium nitrate, stirring, diluting with water, and then adding hydrogen peroxide to obtain graphene oxide sheets; washing with hydrochloric acid and water respectively, and vacuum drying at room temperature to obtain dry graphene oxide sheets; Step 3, adding the dried graphene oxide sheet prepared in step 2 to hydrochloric acid, ultrasonicating to obtain a uniform solution, then adding 3,4-(methylenedioxy)aniline to water to obtain solution A, mixing solution A with the uniform solution, stirring at low temperature, adding hydrochloric acid containing ammonium persulfate during stirring, stirring at low temperature, washing with water and anhydrous ethanol until the filtrate is colorless, ultrasonicating, adjusting the pH with ammonia water, washing with water, and drying to obtain a graphene oxide composite material; Step 4, adding carboxymethyl chitosan to water, stirring to obtain a carboxymethyl chitosan solution, adding the dried graphene oxide sheets prepared in step 2 to water and ultrasonicating to obtain a graphene oxide suspension, then adding the graphene oxide suspension to the carboxymethyl chitosan solution, stirring, adding hydrazine hydrate, stirring at high temperature, filtering, washing with water, and freeze-drying to obtain a hybrid nanomaterial; Step 5: Add zinc powder, defoamer, dispersant, organic bentonite, silicon dioxide and pentaethylenehexamine to the emulsion prepared in step 1, stir to form a zinc-based water-based latex; add the hybrid nanomaterial prepared in step 4, N,N'-bis(4-aminophenyl)-1.4-benzoquinonediamine and the graphene oxide composite material prepared in step 3, and stir at room temperature to obtain a graphene anti-corrosion coating.

2. A method for preparing a graphene anticorrosive coating for surface protection of port machinery according to claim 1, It is characterized in that The preparation method is as follows, in parts by weight: Step 1, adding 1 to 1.5 parts of ammonium persulfate, 2 to 3 parts of a surfactant, 0.5 to 1 part of sodium n-hexadecyl sulfate and 0.4 to 0.6 parts of sodium bicarbonate to 30 to 50 parts of water to obtain a mixed solution; then, adding 1 to 3 parts of 2-methylprop-2-enoic acid, 10 to 15 parts of glycidyl methacrylate, 8 to 12 parts of isoeugenol methyl ether, 18 to 22 parts of butyl acrylate, 2 to 2.5 parts of a silane coupling agent KH-570, 0.4 to 0.6 parts of N, N'-methylenebisacrylamide and 15 to 25 parts of an epoxy resin to 60 to 70 parts of water, stirring to obtain a composite monomer mixture, dripping the mixed solution into the composite monomer mixture at a dripping speed of 0.5 to 2 mL / min, then continuously stirring at 70 to 85° C., cooling to room temperature, adding 20 to 27 wt % ammonia water to adjust the pH value to 7.0 to 8.0, filtering with a molecular sieve to obtain an emulsion; Step 2, adding 1 to 3 parts of graphite to 180 to 220 parts of 70 to 85 wt% sulfuric acid and stirring, then adding 10 to 15 parts of potassium permanganate and 1 to 3 parts of sodium nitrate, stirring, diluting with 800 to 1200 parts of water, and then adding 8 to 12 parts of 25 to 33 wt% hydrogen peroxide to obtain graphene oxide sheets; washing with 0.5 to 2 mol / L hydrochloric acid and water for 1 to 3 times respectively, and vacuum drying at room temperature to obtain dry graphene oxide sheets; Step 3, adding 0.05-0.2 parts of the dried graphene oxide sheet prepared in step 2 to 15-25 parts of 0.5-2 mol / L hydrochloric acid, ultrasonicating to obtain a uniform solution, and then adding 0.5-2 parts of 3,4-(methylenedioxy)aniline to 15-25 parts of water to obtain solution A, mixing solution A with the uniform solution, stirring at 1-5°C, adding 4-6 parts of 0.5-2 mol / L hydrochloric acid containing 0.5-2 parts of ammonium persulfate during the stirring process, stirring at 1-5°C, washing with water and anhydrous ethanol until the filtrate is colorless, ultrasonicating, adjusting the pH to 10-11 with 20-27wt% ammonia water, washing with water, and vacuum drying at 70-85°C for 10-30h to obtain a graphene oxide composite material; Step 4, adding 0.1-0.3 parts of carboxymethyl chitosan to 90-110 parts of water, stirring to obtain a carboxymethyl chitosan solution, adding 0.1-0.3 parts of the dried graphene oxide sheets prepared in step 2 to 80-120 parts of water for ultrasonication to obtain a graphene oxide suspension, then adding 80-120 parts of the graphene oxide suspension to the carboxymethyl chitosan solution, stirring, adding 0.1-0.3 parts of hydrazine hydrate, stirring at 80-95° C., filtering, washing with water, and freeze-drying to obtain a hybrid nanomaterial; Step 5, adding 40-60 parts of zinc powder, 0.3-0.5 parts of defoaming agent, 0.6-0.7 parts of dispersant, 1-3 parts of organic bentonite, 0.1-0.2 parts of silicon dioxide, and 0.1-0.2 parts of pentaethylenehexamine to 20-30 parts of the emulsion prepared in step 1, stirring to form a zinc-based water-based latex; adding 0.2-0.4 parts of the hybrid nanomaterial prepared in step 4, 0.4-0.6 parts of N,N'-bis(4-aminophenyl)-1.4-benzoquinonediamine, and 0.4-0.6 parts of the graphene oxide composite material prepared in step 3, and stirring at room temperature to obtain a graphene anti-corrosion coating.

3. A method for preparing a graphene anticorrosive coating for surface protection of port machinery according to claim 1 or 2, It is characterized in that The surfactant is at least one of OP-10, NP-9 or AES.

4. A method for preparing a graphene anticorrosive coating for surface protection of port machinery according to claim 1 or 2, It is characterized in that The molecular sieve is 800-1000Da.

5. A method for preparing a graphene anticorrosive coating for surface protection of port machinery according to claim 1 or 2, It is characterized in that The defoaming agent is at least one of SXP-105, SN-345, BYK-045 and BYK-141.

6. A method for preparing a graphene anticorrosive coating for surface protection of port machinery according to claim 1 or 2, It is characterized in that The dispersant is at least one of SN-5040, GH5050, DP512, BYK-110, DisuperS18, DisuperS19, and DisuperS31.

7. A method for preparing a graphene anticorrosive coating for surface protection of port machinery according to claim 1 or 2, It is characterized in that The stirring speed is independently 100 to 500 rpm, and the stirring time is independently 0.1 to 72 h.

8. A method for preparing a graphene anticorrosive coating for surface protection of port machinery according to claim 1 or 2, It is characterized in that The ultrasonic time is independently 10 to 60 minutes, the ultrasonic frequency is independently 20 to 60 kHz, and the ultrasonic power is independently 100 to 400 W.

9. A graphene anti-corrosion coating for port machinery surface protection, It is characterized in that The preparation method is as described in any one of claims 1 to 8.

10. An application of the graphene anti-corrosion coating for surface protection of port machinery as claimed in claim 9, It is characterized in that Mainly used in marine engineering facilities; the marine engineering facilities include offshore facilities, coastal and bay structures, offshore oil platforms, and boats.